Pemanfaatan Kotoran Sapi Menjadi Biogas Sebagai Upaya Pengendalian Limbah Peternakan - Fidela, Wita; Ahda, Yuni; Zhafira; Febriani, Yusi; Azzahra, Yolanda; P. Ningky, Yiyin; T. Berlian; Regina; K. Sari, Jelly; Ayu, Duni; D. N. Putri, Dini; Fajrina, Suci (Jurnal Ekologi, Masyarakat dan Sains, 2024)
Cows are mammals that are widely bred throughout Indonesia. The large number of cattle breeders in Indonesia has positive and negative sides when viewed from various points of view. Cattle farming generally produces livestock waste, especially manure. Cow dung can be used as a basic ingredient for alternative energy production in the form of biogas. However, in reality, many cattle breeders ignore the problem of animal waste and it is wasted, even causing pollution to the environment. This research aims to test the use of cow dung as the main organic material in biogas production as a sustainable effort to minimize the environmental impact due to livestock waste and as an alternative energy. This research uses an experimental method with a biogas production trial for 21 days using a simple digester. The research results show that cow dung has great potential as a raw material for making biogas. Other factors influence biogas production, such as acidity levels, environmental temperature, and manure conditions.